2021
DOI: 10.1016/j.ctro.2020.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Bladder preserving chemoradiotherapy compared to surgery for variants of urothelial carcinoma and other tumors types involving the bladder: An analysis of the National Cancer Database

Abstract: Highlights Muscle invasive bladder cancer with variant histology has worse outcomes. Chemoradiation is associated with similar OS to surgery for variant histology. Adenocarcinoma and SCC have worse OS associated with chemoRT compared to surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Few reports compared cancer control outcomes after TMT between UCUB and non-urothelial VH patients [ 10 , 11 ]. We addressed this void and hypothesized that no differences would distinguish VH from UCUB in TMT-treated T2N0M0 patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few reports compared cancer control outcomes after TMT between UCUB and non-urothelial VH patients [ 10 , 11 ]. We addressed this void and hypothesized that no differences would distinguish VH from UCUB in TMT-treated T2N0M0 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, NCDB only allows overall survival analyses and CSM cannot be distinguished from other-cause mortality. In a different study, which also focused on TMT-treated patients, Janopaul-Naylor et al [ 10 ] (NCDB 2004–2015) tested for overall survival differences in RC- and TMT-treated patients according to different histological subtypes. The authors reported worse overall survival for squamous cell carcinoma TMT-treated patients (n = 94, HR 1.49, 95% CI 1.25–1.77, p < 0.001) as well as for adenocarcinoma TMT-treated patients (n = 38, HR 1.75, 95% CI 1.36–2.25, p < 0.001) vs. their RC counterparts harboring the same histological subtype.…”
Section: Discussionmentioning
confidence: 99%
“…Those with bladder cancer with adenocarcinoma or squamous cell carcinoma had worse survival outcomes associated with bladder preservation therapy compared to cystectomy. 13 better OS compared to those receiving CCRT before propensity score matching, whereas OS was similar between groups after propensity score matching. 14 In a retrospective multi-institutional study, Zlotta et al found no differences in CSS and DFS between radical cystectomy and bladder preservation therapy.…”
Section: Discussionmentioning
confidence: 88%
“…Fully 30%–40% of their patients had non‐urothelial histologic types of diseases. Those with bladder cancer with adenocarcinoma or squamous cell carcinoma had worse survival outcomes associated with bladder preservation therapy compared to cystectomy 13 . Lin et al.…”
Section: Discussionmentioning
confidence: 99%
“…Most chemoradiation regimens for MIBC employ concurrent cisplatin with significant remissions and better survival [21]. Survival rates are similar to those achieved by primary cystectomy [22] and have proven superior for T3b and T4 tumors [23].…”
Section: Discussionmentioning
confidence: 98%